Microplastics Pollution in Chile: Current Situation and Future Prospects - Paredes-Osses, Esteban; Pozo, Karla; Opazo-Capurro, Andrés; Bahamonde, Paulina; Cabrera-Pardo, Jaime R. (Frontiers in Environmental Science, 2021)
Millions of tons of plastics enter wild habitats, especially the oceans, every year. Despite extensive efforts, this amount is predicted to increase over in the near future, leading to a catastrophic damage to the environment. Small plastic fragments, including microplastics, are currently widely distributed in different environments and contribute significantly to pollution of the oceans. This problem is particularly poignant in Chile, a country with more than 4,000 km of coastline along the Pacific Ocean home to diverse environments, industrial activities and unique biodiversity. In this review, we compile information regarding microplastics pollution in Chilean environments in terms of transport, distribution and bioaccumulation along the country, societal actions such as environmental policies and education to tackle the plastic problem, and the Trojan effect associated with it. Finally, we identify critical scientific gaps, such as the transport of harmful chemicals and microbial communities associated, and define potential future research directions.